2011
DOI: 10.1093/heapol/czr026
|View full text |Cite
|
Sign up to set email alerts
|

Composition of pluralistic health systems: how much can we learn from household surveys? An exploration in Cambodia

Abstract: In spite of all efforts to build national health services, health systems of many low-income countries are today highly pluralistic. Households use a vast range of public and private health care providers, many of whom are not controlled by national health authorities. Experts have called on Ministries of Health to re-establish themselves as stewards of the entire health system. Modern stewardship will require national and decentralized health authorities to have an overall view of their pluralistic health sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 20 publications
4
44
0
1
Order By: Relevance
“…In general, Cambodian people tend to visit over-the-counter drug stores for their health problem. This is in accordance with the prepondence of studies that have demonstrated patronage of drug stores and the private sector in preference to the public health system in Cambodia (Meessen et al, 2011). This trend is not new, especially in low-income setting where the health system is pluralistic.…”
Section: Discussionsupporting
confidence: 87%
“…In general, Cambodian people tend to visit over-the-counter drug stores for their health problem. This is in accordance with the prepondence of studies that have demonstrated patronage of drug stores and the private sector in preference to the public health system in Cambodia (Meessen et al, 2011). This trend is not new, especially in low-income setting where the health system is pluralistic.…”
Section: Discussionsupporting
confidence: 87%
“…From a public policy point of view, it appears more appropriate to try to rationalize the practice than to attempt (often in vain) to prohibit it. In this context, one option would be to focus regulatory efforts on a limited list of drugs whose contraindications and risks are significant [5] and develop programs to promote self-medication practices for mild health problems. Experiments of this type of practice in the DR Congo have already been documented in the two rural HDs of Kasongo and Bwamanda [36].…”
Section: Discussionmentioning
confidence: 99%
“…In South-East Asia, U5MR declined from 72 to 27 per 1,000 live births during the period 1990–2015, where NMR declined from 28 to 13 per 1,000 live births during the same time span [3] [4]. Changes in the levels of infant and child mortality also differed by socio-economic status of the household and level of education of the mother and various studies attribute declines in mortality to the combined effects of improved health care practices and socio-economic advancements [5] [6] [7]. In Cambodia, data from Demographic and Health Surveys (DHS) show a substantial decline in mortality rates; yet, NMR remains high at 18 per 1,000 live births [4] [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%